2017
DOI: 10.1177/0963689717722787
|View full text |Cite
|
Sign up to set email alerts
|

Does the Mesenchymal Stem Cell Source Influence Smooth Muscle Regeneration in Tissue-Engineered Urinary Bladders?

Abstract: A variety of tissue engineering techniques utilizing different cells and biomaterials are currently being explored to construct urinary bladder walls de novo, but so far no approach is clearly superior. The aim of this study was to determine whether mesenchymal stem cells (MSCs) isolated from different sources, (bone marrow [BM-MSCs] and adipose tissue [ADSCs]), differ in their potential to regenerate smooth muscles in tissue-engineered urinary bladders and to determine an optimal number of MSCs for urinary bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…Looking closer at the different bladder wall components in the regenerated tissue, we unexpectedly found that SMC bundle formation was more pronounced in the samples seeded with 1 × 10 6 cells and the control. This is in contrast with the findings of Pokrywczynska who showed that a higher density of MSCs significantly improved the smooth muscle content in tissue-engineered urinary bladders after 3 months (Pokrywczynska et al, 2017). A possible explanation could be the earlier time point in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Looking closer at the different bladder wall components in the regenerated tissue, we unexpectedly found that SMC bundle formation was more pronounced in the samples seeded with 1 × 10 6 cells and the control. This is in contrast with the findings of Pokrywczynska who showed that a higher density of MSCs significantly improved the smooth muscle content in tissue-engineered urinary bladders after 3 months (Pokrywczynska et al, 2017). A possible explanation could be the earlier time point in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…We and other authors have demonstrated, that unseeded grafts do not allow for proper urinary bladder regeneration (Pokrywczynska et al, 2017). However, these papers were mainly using SIS (Chung et al, 2005;Pokrywczynska et al, 2017) or synthetic materials (Horst et al, 2017;Jack et al, 2009) and all used a cystoplasty model with full thickness replacement of the bladder wall. This might explain the different findings.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that source of mesenchymal stem cells (bone morrow vs adipose tissue) had no impact on regeneration of tissue-engineered urinary bladder. However, regeneration outcome is strictly dependent on the number of cells used for the reconstruction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore urothelial cells could not only prevent an urine leakage to the deeper graft layers by biomaterial sealing but also protect smooth muscle cells or mesenchymal stem cells seeded on the outer graft surface from cytotoxic effect of urine (Pokrywczynska et al, 2017(Pokrywczynska et al, , 2018b. It was indicated that urothelial cells are more resistant to urine compared to smooth muscle cells or mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that urothelial cells are more resistant to urine compared to smooth muscle cells or mesenchymal stem cells. Therefore urothelial cells could not only prevent an urine leakage to the deeper graft layers by biomaterial sealing but also protect smooth muscle cells or mesenchymal stem cells seeded on the outer graft surface from cytotoxic effect of urine (Pokrywczynska et al, 2017(Pokrywczynska et al, , 2018b.…”
Section: Introductionmentioning
confidence: 99%